Effect of combined mental and physical training on the targeting accuracy of patients with multiple sclerosis - Kambiz Mam Sheikh; Sarkawt Kolahdouzi; Hamid Foroghi Pour; Muhammad Tahir Abbasi Rad (Gonabad University of Medical Sciences, 2017)
Multiple Sclerosis (MS) is a chronic disease of the central nervous system, and is cause of motor deficits and physical disability in young adults. This study aimed to determine the effect of combined mental and physical training on the targeting accuracy of patients with MS. This study was conducted on 41 patients with MS (31 women and 10 men) aged 20-50 years, the members of the MS society. The participants were selected through purposive sampling and were randomly divided into four groups of mental training (n=10), physical training (n=11), combined (mental-physical) training (n=11), and the control group (n=9). Dart throwing test was used to evaluate the targeting accuracy of the participants. Expanded disability status scale was used to measure the degree of disability in patients and vividness of movement imagery questionnaire-2 was used to assess the movement imagery ability. Training was performed for 8 weeks (three 15-minute sessions per week). Before and after 8 weeks, the participants. were tested on dart-throwing ability. The targeting accuracy of all training groups was significantly improved compared with the control group. A significant difference was observed in the level of improvement between the combined training group and other groups, but no significant difference was observed between the mental training group and the physical training group. Compared to other methods, combined mental and physical training can be more effective in improving the dart-throwing accuracy of MS patients.